-6(w-8)-(9+8w)=-15w

Simple and best practice solution for -6(w-8)-(9+8w)=-15w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(w-8)-(9+8w)=-15w equation:


Simplifying
-6(w + -8) + -1(9 + 8w) = -15w

Reorder the terms:
-6(-8 + w) + -1(9 + 8w) = -15w
(-8 * -6 + w * -6) + -1(9 + 8w) = -15w
(48 + -6w) + -1(9 + 8w) = -15w
48 + -6w + (9 * -1 + 8w * -1) = -15w
48 + -6w + (-9 + -8w) = -15w

Reorder the terms:
48 + -9 + -6w + -8w = -15w

Combine like terms: 48 + -9 = 39
39 + -6w + -8w = -15w

Combine like terms: -6w + -8w = -14w
39 + -14w = -15w

Solving
39 + -14w = -15w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '15w' to each side of the equation.
39 + -14w + 15w = -15w + 15w

Combine like terms: -14w + 15w = 1w
39 + 1w = -15w + 15w

Combine like terms: -15w + 15w = 0
39 + 1w = 0

Add '-39' to each side of the equation.
39 + -39 + 1w = 0 + -39

Combine like terms: 39 + -39 = 0
0 + 1w = 0 + -39
1w = 0 + -39

Combine like terms: 0 + -39 = -39
1w = -39

Divide each side by '1'.
w = -39

Simplifying
w = -39

See similar equations:

| 5y-3(y-1)= | | -3y-10=5x+14 | | 6/3=y/6 | | 1100=1220-20p | | 9x-17=100 | | 48/k=8/5 | | -4+10=16x-2-15x | | 6(x-3)=9+5x | | 4pq+q= | | 2/7a=7 | | 2-y=19 | | 8-2(4-3m)= | | 24+x-6=50+6 | | 7(y+2)+y=4(y+2)+7 | | 8y=3y+18 | | d^2+5/2d+3/2=0 | | 6x+6-2x=1+3x-1 | | 6y=4x | | 28ab-7a-8b+2= | | -250.00+75.00w=500.00 | | 9-5x=3x-46 | | x^1/3=0 | | 5/6x=-10 | | (4x-2)=90 | | x^4-3-x^3+125=0 | | 5z=12-22 | | 4x^2-1-x(2x+1)=0 | | 1+(x-3)/3=(2x+1)/6-2 | | 0=3y^2-19y+22 | | 2x+8=-31+7x | | x^9+6-2x^5=1 | | 5v=3(v-1)+(3+2v) |

Equations solver categories